Designing a Model for Enhancing the Reputation of Online Brands - Asadi, Hossein; Mahmoudzadeh Vashan, Mehdi; Hakimpour, Hossein; Rezaeifar, Hamid (Management Strategies and Engineering Sciences, 2025)
Online reputation or electronic reputation can be considered one of the most significant intangible assets of companies. The objective of this study is to design a model for enhancing the reputation of online brands. The present research is qualitative in terms of methodology and employs a descriptive-exploratory approach with a phenomenological method for data analysis. The research instrument used in this study is in-depth (semi-structured) interviews. The statistical population consists of 10 experts and specialists in the field of marketing for online brands. In this study, members of the expert panel were selected using a purposive sampling approach. Key codes were extracted through a thematic analysis approach and analyzed using MAXQDA software. The validity of the research findings was assessed and confirmed based on the criteria proposed by Creswell (2002). The results indicated that the categories and components of online brand reputation enhancement include 11 main categories: online brand reputation, cultural factors, customer experience management, website quality, website security, store social responsibility, social media marketing, content marketing, targeted and intelligent advertising, product and service quality, and customer satisfaction, along with 63 subcategories.